Quality of life as a fundamental outcome after curative intent gastrectomy for adenocarcinoma: lessons learned from patients - Pinheiro, Rodrigo Nascimento (J Gastrointest Oncol, 2019)
BACKGROUND: Gastric cancer has an important epidemiologic impact, and the main curative therapeutic modality for gastric cancer is surgical resection. However, even curative intent therapy can have negative effects on the quality of life (QoL) of these patients, which is undesirable; thus, it is difficult to balance the standardized treatment reported in the literature and treatment response to achieve full patient satisfaction. The purpose of our study was to evaluate the QoL and identify the association of scores on the Functional Assessment of Cancer Therapy-Gastric (FACT-Ga) and Short Form 36 Health Survey version 2 (SF36v2) questionnaires with sociodemographic, clinical and anatomopathological aspects of gastric adenocarcinoma patients undergoing curative surgery. METHODS: This was a cross-sectional study involving 104 patients from three regions of Brazil. Inferential analyses were used to compare (multiple regression and Mann-Whitney or Kruskal-Wallis tests) the relationships between these scores and variables (Spearman’s coefficient). RESULTS: In the multiple regression analysis, we found correlations between Helicobacter pylori status and physical well-being (PWB) (P=0.026), between gender and emotional well-being (EWB) (P=0.008), between Lauren’s histology and physical functioning (P=0.009), as well as the Short Form 36 Health Survey version 2 (SF-36v2) role-physical (P=0.027), between the tumor site and EWB (P=0.038), between the SF-36v2 mental health and N (the lower the staging, the better the score, P=0.006) and between the SF-36v2 mental health and lymph nodes removed (P=0.029). According to the Mann-Whitney or Kruskal-Wallis test, women had worse FACT-Ga total (P=0.049), PWB (P=0.005), EWB (P=0.007), gastric cancer subscale (GaCS, P=0.011), trial outcome index (TOI, P=0.030) and mental health scores than men (P=0.011). Patients with distal tumors had better scores (FACT-Ga, P=0.018; GaCS, P=0.014; TOI, P=0.020) than patients with proximal tumors. Patients with tumors located in the cardia had better physical functioning than those with proximal tumors (P=0.042). Patients who underwent partial gastrectomy had better FACT-Ga total scores (P=0.011), PWB (P=0.033), GaCS scores (P=0.006) and TOI scores (P=0.008) than those who underwent total gastrectomy. Patients who did not receive adjuvant therapy had worse bodily pain as reported on the SF-36v2 than those who received therapy (P=0.048). According to Spearman’s coefficient, a higher lymph node stage corresponded to worse FACT-Ga total (s=−0.200, P=0.034), GaCS (s=−0.206, P=0.037), TOI (s=−0.216; P=0.028) and vitality (s=−0.215, P=0.029) scores. A longer time after treatment corresponded to a better SF-36v2 role-physical domain score (s=0.223; P=0.023). CONCLUSIONS: The type of treatment instituted, postoperative time and sociodemographic and anatomopathological factors influence the QoL.